Physical function and sex differences in radiographic axial spondyloarthritis: a cross-sectional analysis on Bath Ankylosing Spondylitis Functional Index - Magnus Hallström; Eva Klingberg; Anna Deminger; Jeannette Beckman Rehnman; Mats Geijer; Helena Forsblad-d’Elia (Arthritis Research & Therapy, 2023)
Abstract Background Physical function is an important determinant of health-related quality of life in radiographic axial spondyloarthritis patients (r-axSpA). To improve the basis of effective healthcare efforts, we aimed to investigate which demographic and disease-related factors that influence Bath Ankylosing Spondylitis Functional Index (BASFI) in r-axSpA patients overall and stratified by sex. Furthermore, we sought to explore differences between sexes regarding separate BASFI questions and also to explore which factors that may contribute to these differences. Methods This observational cross-sectional study included patients fulfilling the modified New York criteria for Ankylosing Spondylitis. Patients were assessed with 66/68 joint count and Bath Ankylosing Spondylitis Metrology Index (BASMI) measurements. Lateral X-rays were performed for Modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS). Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Ankylosing Spondylitis Disease Activity Score (ASDAS)-C-Reactive Protein (CRP), and BASFI were registered. Multivariable linear regression analyses were used to investigate which factors that associate with BASFI. Results A total of 353 r-axSpA patients were included, mean age 52.2 ± 12.7 years, 62.3% males. No significant sex difference was seen in BASFI scores (2.7 ± 2.0 in males vs 2.9 ± 2.1 in females). Age, body mass index, ASDAS-CRP, BASMI or mSASSS, fatigue, and tenderness were found to associate independently with BASFI in different models (R 2 0.53–0.63). Investigation of separate BASFI questions revealed that the ability to look over shoulder was worse in males than females (mean 4.43 ± 3.37 vs 3.74 ± 3.06, p = 0.05) and most strongly correlated with mSASSS and BASMI among separate BASFI questions (r = 0.53, p < 0.001; r = 0.62, p < 0.001). The ability to climb stairs was worse in females than males (mean 2.49 ± 2.77 vs 1.54 ± 2.32, p < 0.001). Conclusions No difference between male and female r-axSpA patients was seen in BASFI despite significant sex differences in BASMI, mSASSS, and CRP levels. Our results underline the impact of fatigue and tenderness on BASFI. The ability to climb stairs without a handrail was scored worse among females compared to males. Furthermore, the ability to look over the shoulder was worse in males than females and closely related to spinal mobility and structural spinal changes.